2022
DOI: 10.1007/s00393-022-01233-1
|View full text |Cite
|
Sign up to set email alerts
|

Birmingham Vasculitis Activity Score und der Short Form 36-Item Health Survey als Prädiktoren aktueller depressiver Störungen bei Patienten mit antineutrophile-zytoplasmatische-Antikörper-assoziierter Vaskulitis während der SARS-CoV-2-Pandemie

Abstract: Introduction This study compared the frequency and severity of depressive disorders in patients with antineutrophil cytoplasmic antibody-associated vasculitis (AAV) before and during the severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) pandemic using the Korean version of the Center for Epidemiologic Studies Depression Scale-Revised (K-CESD-R) and the Korean version of the Profile of Mood States (K-POMS) depression, and further determined predictors of current depressive disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It is important to contextualize that the present study was conducted during the SARS-CoV-2 pandemic, which severely impacted Mexico as the rest of the world, resulting in an increased frequency of depressive disorders, limitations in daily life, and socioeconomic difficulties. Recent data have shown that outcome measurements in AAV patients, such as the BVAS score, were predictors of current depressive disorders during the pandemic, unlike those before the pandemic [ 32 ]. Therefore, it would be interesting to assess the AAV-PRO questionnaire and disease activity in the future to assess the variability in illness perceptions over time.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to contextualize that the present study was conducted during the SARS-CoV-2 pandemic, which severely impacted Mexico as the rest of the world, resulting in an increased frequency of depressive disorders, limitations in daily life, and socioeconomic difficulties. Recent data have shown that outcome measurements in AAV patients, such as the BVAS score, were predictors of current depressive disorders during the pandemic, unlike those before the pandemic [ 32 ]. Therefore, it would be interesting to assess the AAV-PRO questionnaire and disease activity in the future to assess the variability in illness perceptions over time.…”
Section: Discussionmentioning
confidence: 99%